1998
DOI: 10.1007/s002130050631
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking on acoustic prepulse inhibition in healthy men and women

Abstract: Acoustic prepulse inhibition (PPI) refers to the reduction of the startle reflex to an intense stimulus if it is preceded by a weak stimulus. Nicotine and smoking have been reported to enhance PPI in rats and in healthy men, respectively. We studied the influence of smoking on PPI in healthy men and women, comparing non-smokers, deprived smokers, and smokers smoking during the test session after deprivation or after ad libitum smoking. Smoking during the session enhanced PPI, without affecting startle reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 38 publications
5
35
1
Order By: Relevance
“…Another factor moderating PPI in several reports is smoking status (Della Casa et al 1998). Our sample included very few smokers, based on the demographics recruited for several of our drug studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor moderating PPI in several reports is smoking status (Della Casa et al 1998). Our sample included very few smokers, based on the demographics recruited for several of our drug studies.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported that PPI is elevated among active smokers (Kumari et al 1996; Della Casa et al 1998; Duncan et al 2001; Swerdlow et al 2006a) and among non-smokers after acute nicotine challenge (Kumari et al 1997; Drobes et al 2013). Because of this, smokers are generally excluded from our drug challenge studies, though more recently this criterion has been removed in order to more closely match the smoking histories of healthy subjects with those of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of nicotine on prepulse inhibition have also been examined in nondeprived smokers. Della Casa, Hofer, Winer, and Feldon (1998) found that smoking during a test session enhanced prepulse inhibition among nondeprived smokers, and that nicotine's effects were not magnified among smokers first deprived of nicotine. These results suggest that cigarette smoking may enhance attention among regular smokers.…”
Section: Cognitive-affective Vulnerability Mechanismsmentioning
confidence: 98%
“…In human smokers there is no evidence of such potentiation of “baseline” startle (Della Casa, Hofer, Weiner, & Feldon, 1998; Duncan et al, 2001; Grillon, Avenevoli, Daurignac, & Merikangas, 2007; Hogle & Curtin, 2006; Mueller, Mucha, & Pauli, 1998), likely due to large individual differences in startle amplitude. In some studies, however, abstinent smokers have shown greater potentiated startle to aversive cues (Cinciripini et al, 2006; Grillon et al, 2007; Hogle & Curtin, 2006), which suggests that drug deprivation alters the response of brain motivational systems to the presentation of negative emotional cues.…”
mentioning
confidence: 98%